Women's Psychic Violence in the Buru Island Tetralogy by Pramoedya Ananta Toer - Marwan, Rafli; Nuryatin, Agus; Doyin, Mukh (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
The Tetralogy of Buru Island by Pramoedya Ananta Toer discusses various forms of psychological violence. However, various studies that the authors found have not addressed this issue. Whereas, women?s psychological violence is very important in developing literacy research that contributes to the resolution of women's problems. The purpose of this study was to analyze psychological violence in women in the Buru Island Tetralogy by Pramoedya Ananta Toer, along with psychiatric symptoms. This research uses a feminist approach to psychoanalysis. The research data are in the form of a Tetralogy of Buru Island by Pramoedya Ananta Toer. The source of research data is the Tetralogy of Buru Island by Pramoedya Ananta Toer. Data analysis was performed qualitatively with heuristic and hermeneutic reading techniques. From the results of the study found a form of psychological violence as follows: sexual violence in the form of sexual abuse experienced by Annelies, while sexual violence was experienced by Nyai Ontosoroh, Annelies, and Maiko characters; emotional abuse experienced by Nyai Ontosoroh and Paulette; economic violence experienced by Nyai Ontosoroh. Furthermore, psychiatric symptoms experienced are hysterical, traumatic, and depression.